Face and trust: A semiotic inquiry into influencers, money, and amygdala - Bankov, Kristian (Sign Systems Studies, 2021)
After the cultural explosion of Web 2.0, digital culture reveals an apparently semiotic paradox associated with the incredibly widespread use of images of faces, while at the same time the reason to trust in the authenticity of these faces is constantly declining. This is because graphic technology has made the sophisticated manipulation of images both possible and easy. After a review of the existing semiotic models and considerations of trust, I am proposing a new approach which emphasizes the value-generating properties of trust by analogy with the money sign, seen as “trust inscribed”. Research from the neurosciences supports the hypothesis that the trustworthiness of the face is judged pre-reflexively and primordially. This, therefore, means that a trustworthy face is a premise for more successful communication than an untrustworthy one, notwithstanding the object of discussion and the cultural context. An example concerning social media influencers serves to show that in the internet-dominated globalizing culture, trustworthy faces are a multipurpose communicative asset that makes a difference.